Efficacy and Safety of Mucopolysaccharide Polysulfate Cream for Non-Exudative Eczema: A Systematic Review and Meta-Analysis - Li, Ming; Li, Yan; Xiang, Lujing; Li, Linfeng (Frontiers in Medicine, 2021)
Background: Mucopolysaccharide polysulfate (MPS) cream as a moisture is widely applied to treat eczema, and a lot of clinical trials have demonstrated its efficacy and safety. However, there is no further research to collect and analysis these studies. Objective: This meta-analysis aimed to assess the efficacy and safety of MPS cream as a monotherapy or add-on therapy for nonexudative eczema. Methods: Eight databases were searched to identify the eligible randomized controlled trials from their inception to July 31, 2021. Revman 5.3 software was used for the meta-analysis. Results: A total of eligible 20 studies were included. 2 studies compared MPS cream with other moistures, 14 compared MPS cream plus topical corticosteroid (TCS) with TCS alone,4 compared with MPS cream plus tacrolimus ointment with tacrolimus ointment alone. The pooled results demonstrated that MPS cream had a significantly higher total efficacy rate (Risk ratio [RR] 1.21, 95% confidence interval [CI]: 1.12 to 1.30, P<0.00001), lower recurrence rate (RR 0.04, 95%CI: 0.26 to 0.74, P=0.002) and lower pruritus score (mean difference [MD] -1.78, 95%CI: -2.16 to -1.40, P<0.00001) than urea cream or vaseline ointment. Moreover, in comparison with TCS or tacrolimus ointment alone, the combination treatment performed better in terms of total efficacy rate, total symptom score, recurrence rate and pruritus score. For safety, the skin adverse events were mild, and the rates of MPS cream as a monotherapy or add-on therapy were comparable to or less than those of the control treatments. Conclusions: MPS cream as a monotherapy or add-on therapy could provide a good effect for the treatment of nonexudative eczema with mild and tolerable skin adverse events. However, due to suboptimal quality of the included studies, high-quality and large-sample RCTs are needed in the future for update or validation.